Effect of nationwide concurrent drug utilization review program on drug-drug interactions and related health outcome - Kim, Dong Sook; Je, Nam Kyung; Park, Juhee; Lee, Sukhyang (International Journal for Quality in Health Care, 2021)
Background: A computerized drug utilization review (DUR) program has provided physicians and pharmacists with alerts on drug-drug interactions (DDIs), drug-age precautions and therapeutic duplication in Korea since 2010. Objective: The purpose of this study was to evaluate the impact of the DUR program on health outcomes associated with DDIs. Methods: An uncontrolled before-after study was performed to investigate the impact of the nationwide DUR program on DDIs and related health outcomes. The study population consisted of people who used two types of DDI pairs before DUR implementation (from January 2009 to December 2010) and post-DUR implementation (from January 2012 to December 2013); (i) benzodiazepines with concurrent use of metabolic enzyme inhibitors and (ii) QTc (heart-rate corrected QT interval) prolongation agents. The main outcome measures were all-cause and cause-specific hospitalization admissions or emergency department (ED) visits. Results: This study included 107 874 people who used benzodiazepines with enzyme inhibitors and 8489 who received co-medication of QTc prolongation agents. For patients receiving a combination of benzodiazepines and enzyme inhibitors, both all-cause hospitalization and cause-specific hospitalization decreased after DUR implementation, from 43.2% to 41.7% and from 4.6% to 4.5% (adjusted odds ratio [OR] = 0.96; 95% confidence interval (CI), 0.93-0.98; OR = 0.89, 95% CI = 0.84-0.99, respectively). For patients receiving co-medication of QTc prolongation agents, all-cause hospitalization (54.2%) was lower than before (54.9%) (OR = 0.87, 95% CI = 0.79-0.96), but no significant change was found for cause-specific hospitalization and ED visits. Conclusion: Implementation of a DUR program may reduce the adverse health outcomes posed by DDIs in patients on combination of benzodiazepines and enzyme inhibitors potentially QTc-prolongation agents.
Keywords: Drug Interactions; Drug Utilization Review; Drug-Related Side Effects and Adverse Reactions; Humans; Outcome Assessment, Health Care; Pharmaceutical Preparations; drug utilization review; drug-drug interaction; emergency department visit; hospitalization